Common parasite with uncommon associations - Sonal Jain; Jasmita Dass; Monica Sharma; Seema Tyagi (Mediterranean Journal of Hematology and Infectious Diseases)
Filaariasis a quite common in some parts of the world including India. It has been reported as an incidental finding in cytology smears. Here we report three cases where microfilariae of Wuchereria Bancrofti were detected incidentally in bone marrow smears, in two cases in special stain slides. All these patients were being investigated for other hematological disorders.